Modeling the Land Surface Temperature of the Kansas City Metro Area - Gottinger, Paul; Stenz, Tyler; Stewart, Nate (My University, 2011)
We will determine the relationship between land surface characteristics and land surface temperature in and around Kansas City. We will then create a predicted surface temperature map and assess the strength of our models.
Includes Appendices, Figures, Maps and Bibliography.
Keywords: Land Surface Temperature; Modeling; Kansas City